2020
DOI: 10.1088/1402-4896/ab71bf
|View full text |Cite
|
Sign up to set email alerts
|

Study of TAFF and vortex phase of FexTe0.60Se0.40 (0.970 ≤ x ≤ 1.030) single crystals

Abstract: Single crystalline samples with starting compositions FexTe0.60Se0.40 (x = 0.970, 0.985, 1, 1.015 and 1.030) have been grown using the self-flux method to study the effect of Fe variation (x) on the structural and superconducting properties of the grown single crystalline samples. All the grown samples are found superconducting and among all, the FeTe0.60Se0.40 (x = 1) sample shows the highest superconducting transition temperature (TC). For the samples with x other than 1, a decrease in the superconducting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…( 9), the vortex glass temperature T g and critical exponent s were evaluated. According to the vortex-glass theory, s ≤ 2.7 corresponds to the 2D vortex glass state while the values of s in between 2.7 to 8.5 correspond to the 3D vortex glass state [14,17,58]. As represented in Table 2, the obtained s values for different composites are smaller than 2.7, which indicates the 2D vortex glass state for the prepared composites.…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations
“…( 9), the vortex glass temperature T g and critical exponent s were evaluated. According to the vortex-glass theory, s ≤ 2.7 corresponds to the 2D vortex glass state while the values of s in between 2.7 to 8.5 correspond to the 3D vortex glass state [14,17,58]. As represented in Table 2, the obtained s values for different composites are smaller than 2.7, which indicates the 2D vortex glass state for the prepared composites.…”
Section: Tablementioning
confidence: 99%
“…It had been shown that introducing arti cial pinning centers in the superconducting matrices, apart from those which occur naturally, is a very effective method to avoid vortex motion and improve the ux pinning capability and superconducting transport properties [8,10,[27][28][29][30][31]. Different techniques such as chemical doping [17,[32][33][34], high energy ions irradiation [31,35], and different types of additives [1,2,[36][37][38][39][40][41][42][43] were used in the literature for this purpose. It has been proved that the appropriate amount of nanosized additives could improve the microstructure, intergranular coupling, and ux pining capability of the high-temperature ceramic superconductors [2, 36-39, 42, 44, 45].…”
Section: ( )mentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, substantial thermal fluctuations in high-temperature superconductors (HTSCs), vortex phases, and dynamics vary [5,6]. The two distinct vortex phases, such as the liquid and glass phases, respectively, determine the normal and superconducting states [7]. Most of the dynamical complexity of the vortices is due to the battle between thermal fluctuations, arbitrary pinning, and the interaction of vortices [8].…”
Section: Introductionmentioning
confidence: 99%